2016
DOI: 10.1111/echo.13193
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Echocardiographic Epicardial Fat Thickness on Outcomes of Cryoballoon‐Based Atrial Fibrillation Ablation

Abstract: Echocardiographically measured EFT independently predicted the AF recurrence after cryoablation and was also positively correlated with hs-CRP as an indicator for systemic inflammation. Thus, the association of echocardiographically measured EFT with AF recurrence may be linked to systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
(68 reference statements)
0
18
1
Order By: Relevance
“…Most of the articles (7/10) were in the full-text format, while three articles were in the conference abstract [17,19,20]. CT [[15], [16], [17],[19], [20], [21], [22], [23]] and echocardiography [18,24] were the used imaging modalities for EFT measurements. The least sample size was 38 [17], and the largest ones were related to Chao et al, [18] with 283 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the articles (7/10) were in the full-text format, while three articles were in the conference abstract [17,19,20]. CT [[15], [16], [17],[19], [20], [21], [22], [23]] and echocardiography [18,24] were the used imaging modalities for EFT measurements. The least sample size was 38 [17], and the largest ones were related to Chao et al, [18] with 283 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The least sample size was 38 [17], and the largest ones were related to Chao et al, [18] with 283 patients. The first article was published in 2011 [15], and the latest article in 2016 [24] (Table 1). Other characteristics of the included studies including study location, type of ablation, follow-up duration, age, body mass index (BMI), and gender distribution are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 In addition, the relationship between EFT and AF incidence and that between EFT and AF recurrence has been reported in recent years, both after ablation and electrical cardioversion. [14][15][16]21,22 Although no significant difference was observed regarding the median EFT between early and late conversion groups, Obesity has been shown as an independent risk factor for AF. 12,23 However, the association between EpF and AF has been observed to be independent of obesity.…”
Section: Discussionmentioning
confidence: 88%
“…Although it is found to be related with cardiovascular and metabolic risk fac-tors, as in our study [17], a study by Nelson et al [5] revealed a weak correlation between EAT and Framingham risk score and no correlation with subclinical atherosclerosis assessed by carotid intima-media thickness, carotid artery plaque, and coronary artery calcium score. However, recently Canpolat et al [18] clarified that EAT measured by echocardiography independently predicted the AF recurrence after cryoablation and was also positively correlated with high-sensitivity C-reactive protein as an indicator of systemic inflammation. This discrepancy may be due to the different nature of study populations.…”
Section: Discussionmentioning
confidence: 99%